Blended Learning Approach Implementation to Improve Adults’ Tahsin Ability in the Digital Era - Tiarawati, Putri Vidi; Nurhayati, Sri; Hidayah, Siti Nurul; Boriboon, Gumpanat (IAIN Ponorogo, 2023)
This study aims to determine the extent of Tahsin Al-Qur'an learning improvement using a blended learning approach among adult learners at Sekolah Ibu Bandung. This study employed a qualitative approach with a case study method. 13 Tahsin teachers and 130 adult learners participated in this study. From the thorough interview results, observation and document study revealed that after involving 6 phases of blended learning program implementation, the adult learners in all Tahsin levels highly increased their Tahsin learning proficiencies. This blended approach has been met with enthusiasm from both educators and learners, with many lauding its flexibility, active engagement opportunities, and the nurturing mentorship it fosters during face-to-face sessions. The structured design and execution of this program have been pivotal in amplifying learners' comprehension of Tahsin Al-Qur’an concepts. From this study findings, the blended learning approach in Tahsin Al-Qur’an learning can be broadly adopted to general learners to improve their Tahsin aptitudes.